Age Dependent Switching Role of Cyclin D1 in Breast Cancer. (2012) - Rinaldi, Carmela; Malara, Natalia Maria; D'Angelo, Rosalia; Sidoti, Antonina; Leotta, Attilio; Lio, Santo; Caparello, Basilio; Ruggeri, Alessia; Mollace, Vincenzo; Amato, Aldo
Abstract : Background: Cyclin D1 gene (CCND1) plays pivotal roles in the development of several human cancers, including breast cancer, functioning as an oncogene. The aim of this study was to better understand the molecular dynamics of ductal carcinomas with regard to proliferation and the ageing process. Methods: 130 cases of ductal breast cancer in postmenopausal women, aged 52–96 in 3 age classes were selected. Tumoral tissues preserved in formaldehyde solution and subsequently embedded in paraffin were subjected to analysis Fluorescence in situ Hybridization (FISH), Reverse Transcription-Polymerase Chain Reaction (RT- PCR) and immuno-histochemical tests. The molecular variables studied were estimated in relation to the patients' age. Results: The results obtained suggest that the increment of the levels of cyclin D1 in intra-ductal breast tumors in older woman that we have examined is significantly associated with a lower proliferation rate. Conclusion: Cyclin D1, which characterizes tumor in young women as molecular director involved in strengthening tumoral proliferation mechanisms, may be seen as a potential blocking molecular switch in corresponding tumours in old women.